Uncertain lives: Culture, race and neoliberalism in Australia - Stratton, Jon (Cambridge Scholars, 2011)
Introduction: The Neoliberal exclusionary order in Australia: Race, religion and incarceration. Chapters: Two rescues, one history: Everyday racism in Australia; The murderous state: The naturalisation of violence and exclusion in the films of neoliberal Australia; Non-citizens in the exclusionary state: Citizenship, mitigated exclusion and the Cronulla riots; Dying to come to Australia: Asylum seekers, tourists and death; Uncertain lives: Migration, the border and neoliberalism in Australia; “Welcome to paradise”: Asylum seekers, neoliberalism, nostalgia and lucky miles; Trouble with zombies: Muselmänner, bare life and displaced people; Preserving white hegemony: Skilled migration, “Asians” and middle class assimilation.